Insomnia and Gut Microbiota - Nazime Mercan Doğan; Naime Nur Bozbeyoğlu Kart (Türk Uyku Tıbbı Dergisi, 2024)

(untitled)
The gut microbiota are a rich community containing beneficial, pathogenic, or opportunistic pathogenic microorganisms with diverse biochemical abilities. It has many functions such as strengthening gut integrity, protecting against pathogens, obtaining energy, and modulating host immunity. If the composition of the gut microbiota is changed, the relationship between gut integrity and host health is damaged and many neurological mechanisms are disrupted. Insomnia is an important disease that reduces the quality of life and causes many serious diseases from depression to heart attack. Today, the importance of maintaining the delicate balance of gut microbiota has become increasingly evident in order to improve insomnia or alleviate the symptoms of illness. Many factors (nutrition, genetics, age, stress, immunologic gradients, diseases, environment, etc.) affect this balance. In particular, the number and distribution of species in the gut microbiota and the balance of their secondary metabolites are altered with changes in the permeability of the intestinal epithelium in patients with insomnia. The differences in the composition of gut microbiota of patients and healthy people prove the importance of microbiota. Currently, traditional acupuncture applications, probiotic, prebiotic, and symbiotic diets are recommended for the treatment of insomnia, and there is a lot of scientific evidence about the effectiveness of these strategies in regulating gut microbiota. In this review, the close relationship between gut microbiota and insomnia has been explained in the scientific literature. In addition, it contributes to the understanding of microbiota importance in the microbiome-gut-brain axis.